Incubator using Dht11 temperature sensor with iot microcontrol: Perancangan alat inkubator anak burung murai - Nugraha, Irdan; Ramdani, Agus; Pamungkas, Bayu (Jurnal Sistem Informasi Galuh, 2025)
The development of technology and the modernization of electronic equipment along with the progress of the times has caused fundamental changes in human life, where humans now need everything that is completely automatic, practical and effective. It's not only humans who need this practical technology, animals also need this technological equipment to survive. The magpie bird population is an important thing that must be considered, because the large amount of tree felling in the magpie bird's habitat makes it difficult for magpie birds to breed in their habitat. To restore the magpie bird population, now many people are starting to breed magpie birds in their homes to resemble their habitat in the forest, but breeding magpie birds is very difficult. To overcome this problem, it is necessary to design a temperature control device in an IoT-based incubator that can make it easier for magpie bird breeders to regulate the temperature and can monitor the temperature in the incubator via cellphone, so that the magpie chicks that have been separated from their parents can grow well without any problems. physical disabilities or dead magpie chicks so that the magpie bird population can increase.